ФОРМУВАННЯ ІНФОРМАЦІЙНОГО ЗАБЕЗПЕЧЕННЯ ЗАВДАНЬ КЕРУВАННЯ ВИРОБІТКОМ ТА ВІДПУСКОМ ЕЛЕКТРОЕНЕРГІЇ ТЕПЛОЕЛЕКТРОЦЕНТРАЛЛЮ В УМОВАХ ФУНКЦІОНУВАННЯ ЛІБЕРАЛІЗОВАНОГО РИНКУ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ - Коцар, О.В.; Расько, Ю.О. (Інститут електродинаміки НАН України, Київ, 2021)
The liberalization of the electricity market aims at the most complete repletion of consumer needs for electricity and quality power supply, which requires the adaptive management of an energy using both by demand side and by the electricity producers – power plants. The successful solution of this task provides, in particular, for using the effective methods and reliable means for the formation of the informational support for the tasks of managing the power generation and delivery on the power plants in order to ensure conforming in real time the market power bids to current demand side asks. The article proposes a methodology, describes the implemented tools and analyzes the experience of managing the power generation and delivery on the cogeneration power plant based on the information which formed by the automated system for control, metering and energy management in the conditions of functioning of the liberalized electricity market of Ukraine. References 10, figures 5.